A new perspective on the Walser community: - Mathieu Petite (Revue de Géographie Alpine)
This paper focuses on an INTERREG IIIB project to conserve and promote the so-called Walser culture. The case study shows how different stakeholders are involved in a network that transcends national borders. First, the paper analyses how the stakeholders, who previously had no reason to interact with one another, come to work together in constructing common attributes of the Walser heritage, attributes that justify this cooperation. Second, the paper looks at the different ways used by project partners to conserve Walser culture. The role of such a network of partners in social cohesion and economic development is also underlined.